Nutrient supply curves and critical nutrient concentrations for Pinus patula Schl. et Cham. at the nursery stage - Juárez-Mirón, Ferman; López-López, Miguel Ángel; Estañol-Botello, Elizabeth (REVISTA TERRA LATINOAMERICANA, 2021)
Monitoring of the nutrient status of forest seedlings during the nursery stage is critical to ensure plant quality and increase its probability of survival after transplantation. At present, there are no nutritional standards that allow monitoring of the nutrient status of Pinus patula seedlings in the nursery. The objective of the present study was to derive nutrient supply curves as well as a set of foliar critical nutrient concentrations for seedlings of this species. Using the hydroponics sub-irrigation technique, an experiment was set up to provide five increasing concentrations of nitrogen, five of phosphorus, and five of potassium within the nutrient solution for growing Pinus patula seedlings. The Hewitt and Smith formula was used as the base nutrient solution to implement the concentrations of the mentioned elements in the nutrient solution. A complete randomized experimental design was adopted, which had five treatments for each nutrient studied. Each treatment was fourfold replicated, and the experimental unit was a set of eight plants. Results indicate that P. patula plants react according to a sigmoidal pattern to increasing concentrations of an individual nutrient. Based on the sigmoidal models for the seedlings, the concentrations of each nutrient in the nutrient solution, which maximized growth in terms of the several morphological seedling features were derived. The critical foliar concentrations of nitrogen, phosphorus, potassium, calcium, magnesium, iron, copper, zinc, manganese, and boron were also obtained for seedlings of the studied species, whose values were: 2.273% for N, and 2762, 4889, 3287, 981, 86, 4.14, 13.7, 437, and 62 mg kg-1 for P, K, Ca, Mg, Fe, Cu, Zn, Mn, and B, respectively. Nutrient management of seedlings in the nursery influences plant morphology, so that a detailed knowledge of the effects of each nutrient on seedlings can help produce morphologically predesigned plants.